The Relation Between Education And The Types of Foundations - Mishbahuddin, Mohamad; Hidayah, Zia Haninatul (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
Education has an important role in the life of societies and peoples. Interaction and coordination with the surrounding community to contribute effectively, and hence education has occupied many researchers and scholars throughout the ages, and had a considerable amount of study and analysis. Education has a variety of foundations, including cultural, social, historical, religious, economic, scientific and technological, philosophical, political, psychological, and educational. Fundamentals of Education The importance comes with the philosophy of education and sociological education and psychological education and the rest of the branches after it. Given this branches that they are the state, movement and human capacity is focused on education, because they are a field that reflects the applications of education in educational systems and then comes the rest of the educational materials that apply the findings of the foundations of education. Either the relationship between education and culture, or the relationship with religion, or economic and other. Keywords: Relationship, Education, Foundation Of Education